2010
DOI: 10.1002/btpr.453
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of monoclonal antibodies (IgG1) using anionic and anionic/nonionic reverse micelles

Abstract: Purification schemes for antibody production based on affinity chromatography are trying to keep pace with increases in cell culture expression levels and many current research initiatives are focused on finding alternatives to chromatography for the purification of Monoclonal antibodies (MAbs). In this article, we have investigated an alternative separation technique based on liquid-liquid extraction called the reverse micellar extraction. We extracted MAb (IgG1) using reverse micelles of an anionic surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…LP is a basic protein with a pI of about 9-9. Stuckey, 2010;Hilhorst et al, 1992). It was also observed that the size of the RM increases from 8.2 nm for empty RM without protein solubilization to a maximum size of 146.77 nm at pH 8 (Table 1).…”
Section: Effect Of Acid Whey Phmentioning
confidence: 73%
See 1 more Smart Citation
“…LP is a basic protein with a pI of about 9-9. Stuckey, 2010;Hilhorst et al, 1992). It was also observed that the size of the RM increases from 8.2 nm for empty RM without protein solubilization to a maximum size of 146.77 nm at pH 8 (Table 1).…”
Section: Effect Of Acid Whey Phmentioning
confidence: 73%
“…The size of the reverse micelles also increased corresponding to the water content and LP extraction. The larger size protein extracted into the water core of RM requires the adaptation of the reverse micelle size to that of the protein (George & Stuckey, 2010; Hilhorst et al, 1992). It was also observed that the size of the RM increases from 8.2 nm for empty RM without protein solubilization to a maximum size of 146.77 nm at pH 8 (Table 1).…”
Section: Resultsmentioning
confidence: 99%